Numerical Model for Hydration-Lubricated Contact and Its Friction Behavior at Nanoscale - Fang, Yanfei; Ma, Liran; Wang, Xianzhang; Luo, Jianbin (Frontiers in Mechanical Engineering, 2020)
In this study, we propose a numerical model to investigate the contact and friction behaviours of hydration lubricated contact in an aqueous solution confined in a gap of several molecular diameters. A force–distance curve was obtained under different surface forces, and friction behaviour was determined using the modified Eyring thermal activation model. The results showed that the normal boundary contact pressure and contact gaps were obtained using the proposed numerical model. In addition, friction force increased with the logarithm of sliding velocity. Hence, the Eyring model could predict the friction behaviour of hydration lubrication. Moreover, it could capture the underlying physical principles of the contact and friction behaviours of hydration lubrication.